The Effect of Variations in the Composition of Cocoa Shell Charcoal and Peanut Shell Charcoal on Briquette Characteristics - Ahmad Akromul Huda; Tawaqqal, Akbar; Hidayatullah, Syarif; Juniardi, Nurdin (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2025)
Agricultural biomass such as cocoa husks and peanut shells have great potential as raw materials for briquettes to support the provision of sustainable alternative energy. This study aims to evaluate the effect of variations in the composition of these two materials on the characteristics of briquettes, including calorific value, moisture content, ash content, and burning time. The study was conducted using a completely randomized design (CRD) with five treatment compositions (KC1=100:0, KC2=70:30, KC3=50:50, KC4=30:70, KC5=0:100) and three replications. Data were analyzed using Analysis of Variance (ANOVA), and if significant effects were found, the analysis was continued with Duncan’s Multiple Range Test (DMRT) at the 5% level. The results showed that a high proportion of cocoa husk resulted in higher moisture content (15.78%) and lower calorific value (3867 kcal/g), while a high proportion of peanut husk increased the calorific value to 5340 kcal/g and burning time to 84.8 minutes, but was accompanied by higher ash content (17.57%). The balanced mixture of KC3 (50:50) and KC4 (30:70) proved to offer the best compromise, with moisture content <10%, calorific value >4400 kcal/g, burning time >78 minutes, and ash content still within an acceptable range. Thus, although pure peanut shell briquettes (KC5) offer the highest performance, the combination of KC3 and KC4 is more worthy of consideration for improving briquette quality while optimizing the utilization of abundant cocoa shell waste.